How and when to refer patients for oncogenetic counseling in the era of PARP inhibitors. (February 2020) - Neviere, Zoé; De La Motte Rouge, Thibault; Floquet, Anne; Johnson, Alison; Berthet, Pascaline; Joly, Florence
Poly(ADP-ribose)polymerase (PARP) inhibitors are targeted therapy for cancers with homologous repair deficiency (HRD). They were first approved for ovarian cancer and have changed current treatment strategies. They have also demonstrated efficacy in HER2-negative metastatic breast cancer and advanced prostate cancer with BRCA1/2 or ATM mutations. Patients with somatic and/or germline BRCA1/2 mutations benefit more from these treatments than other patients. Nowadays, the diagnosis of HRD is largely based on germline genetic testing, which is performed after an in-person genetic counseling session, even for patients without any family history of cancer. However, with the increasing number of PARP inhibitor indications across different tumor types, rapid access to oncogenetic consultations will become a challenge. To meet this demand, tumor genomic testing could be offered at initial diagnosis. Telephone counseling and other referral systems could replace in-person consultations for certain subgroups of patients deemed to have a low risk of harboring a germline mutation. This article reviews international guidelines for genetic counseling testing. We herein propose new care pathways for breast, prostate and ovarian cancers, including tumor genomic testing at initial diagnosis in order to help triage genetic counseling referrals.